Biological control of white mold by Trichoderma harzianum in common bean under field conditions - Daniel Diego Costa Carvalho; Alaerson Maia Geraldine; Murillo Lobo Junior; Sueli Corrêa Marques de Mello (Pesquisa Agropecuária Brasileira, 2015)
Abstract: The objective of this work was to evaluate Trichoderma harzianum isolates for biological control of white mold in common bean (Phaseolus vulgaris). Five isolates were evaluated for biocontrol of white mold in 'Perola' common bean under field conditions, in the 2009 and 2010 crop seasons. A commercial isolate (1306) and a control treatment were included. Foliar applications at 2x109 conidia mL-1 were performed at 42 and 52 days after sowing (DAS), in 2009, and at 52 DAS in 2010. The CEN287, CEN316, and 1306 isolates decreased the number of Sclerotinia sclerotiorum apothecia per square meter in comparison to the control, in both crop seasons. CEN287, CEN316, and 1306 decreased white mold severity during the experimental period, when compared to the control.